How to read and understand poetry - Spiegelman, Willard; Teaching Company (Springfield, VA : Teaching Co., 1999)
Professor Willard Spiegelman's friendly yet sophisticated approach to poetry has been delighting students at Southern Methodist University for almost thirty years. In the 24 captivating lectures represented here, he invites you to share what he has learned over his distinguished career as a scholar and teacher of literature.
pt. 1: What to look (and listen) for in poems ; Memory and composition ; Poets look at the world ; Picturing nature ; Metaphor and metonymy I ; Metaphor and metonymy II ; Poetic tone ; The uses of sentiment ; The uses of irony ; Poetic forms and meters ; Sound effects ; Three 20th-century villanelles -- pt. 2: Free verse ; The English sonnet I ; The English sonnet II ; The enduring sonnet ; Poets thinking ; The greater romantic lyric ; Poets thinking, some 20th-century versions ; Portrayals of heroism ; Heroism, some 20th-century versions ; Poems talking to (and for) works of art ; Echoes in poems ; Farewells and falling leaves.
In two containers (26 cm.).
Keywords: Poetics; Poetry -- Explication; Poetry -- Themes, motives; Poetry -- History and criticism